Bifunctional semi-closed YF3-doped 1D carbon nanofibers with 3D porous network structure including fluorinating interphases and polysulfide confinement for lithium–sulfur batteries. Issue 44 (31st October 2019) - Hao, Yan; Wang, Liyuan; Liang, Yueyao; He, Benqiao; Zhang, Yaofang; Cheng, Bowen; Kang, Weimin; Deng, Nanping
Abstract : In this study, semi-closed YF3 -doped 1D carbon nanofibers with 3D porous networks (SC-YF3 -doped 3D in 1D CNFs) are fabricated for the first time via electro-blown spinning technology and regarded as cathodes for high performance lithium sulfur cells. Abstract : In this study, semi-closed YF3 -doped 1D carbon nanofibers with 3D porous networks (SC-YF3 -doped 3D in 1D CNFs) are fabricated for the first time via electro-blown spinning technology. The internal 3D porous networks not only offer a stable 3D electrode structure to accommodate the volume expansion, but also enable a high sulfur loading (80%). More importantly, the external semi-enclosed carbon layer maintains outstanding conductivity and further blocks polysulfide diffusion, which significantly breaks the limitation of a traditional carbon matrix. On the other hand, the YF3 nanoparticles are beneficial for forming more uniform fluorinating electrode interphases, achieving the excellent synergistic effect of chemical and physical adsorption to polysulfide. Therefore, the assembled Li–S batteries exhibit a high reversible discharge capacity of 954.2 mA h g −1 with a decay of merely 0.043% per cycle after 600 cycles at 1C rate. Moreover, the discharge capacity decay can be as low as 0.029% per cycle during 800 cycles at a high current density of 2C rate. Even at a high rate of 5C, the cells still possess a favorable capacity of 636.5 mA h g −1 while steadily operating for 700 cycles with a capacity decay rate of merely 0.056%, implying the great potential of this stable semi-closed cathode structure for industrialization.